Analysis of Influence Factor of Soil-Structure Interaction Considered in Pile Analysis using Finite Element Analysis - Kim, Jin; Lee, Jong-Young; Lim, Da-Bi; Han, Jung-Geun (Salehan Institute of Higher Education, 2025)
This study evaluates two often‑overlooked factors in pile analysis (passive earth pressure and the pile-soil contact method) and quantifies their combined influence on load–settlement response, shaft friction, and stress distribution. Conventional finite element analyses rarely consider both passive earth pressure and pile–soil slip simultaneously. This research quantifies the influence of these two factors on the load–settlement behavior, shaft friction, and stress transfer mechanisms of a single square pile. A laboratory model test was conducted using a 50 × 50 × 150 mm model pile embedded in loose sand with a relative density of 25%, and the same conditions were replicated using a 3D FEM model in ANSYS. The soil was modeled using the Mohr–Coulomb model, with parameters obtained from direct shear tests, and the pile was defined as a linear elastic material. The lateral boundaries were defined under two conditions: a general roller-type boundary and a new boundary condition incorporating depth-dependent passive earth pressure. Interface behavior was analyzed with both bonded and frictional contacts. The passive earth pressure boundary condition reduced post-yield settlement error from 22% to 6% and increased calculated shaft friction by 4%, resulting in a post-yield settlement curve that closely matched the experimental results. Bonded contact overestimated the bearing capacity by 17% and produced unrealistic stress concentrations, while Frictional contact accurately reproduced the observed slip surface and ultimate bearing capacity within a 3% margin of error. Parametric analysis revealed that the elastic modulus governed pre-yield stiffness, whereas the friction coefficient primarily influenced plastic deformation behavior. By combining the depth-dependent passive earth pressure boundary with experimentally calibrated frictional contact, this study successfully captured both lateral confinement effects and interface slip, which are typically analyzed separately. Consequently, the predictive accuracy for settlement and bearing capacity of friction piles in sandy soils was empirically improved.